Juvenile and Effective Solutions to Prevent Juvenile Recidivism – Perspectives of Judicial Officers of Vietnam - Tuan, Hoang Minh; Chau, Hoang Xuan; Ngoc, Ha Do; Nguyen, Thang The (Journal of Ecohumanism, 2024)
Juvenile recidivism presents a significant challenge to the criminal justice system in Vietnam. This study examines the perspectives of judicial officers regarding effective solutions to mitigate juvenile reoffending. Through a series of structured interviews and surveys, the research explores judicial officers' insights into the root causes of juvenile delinquency, including socio-economic factors, family influences, and the impact of educational systems. The findings emphasize the importance of rehabilitation over punishment, suggesting that psychological counseling, vocational training, and educational support are pivotal in preventing recidivism. Furthermore, judicial officers advocate for the integration of community-based programs, early intervention strategies, and legislative reforms to address gaps in the juvenile justice system. The study concludes by highlighting the necessity for a multi-disciplinary approach, combining legal, social, and psychological interventions, to effectively curb juvenile recidivism in Vietnam.